Magnitude and Determinants of Antenatal Care Utilization in Kandahar City, Afghanistan - Muhammad Haroon Stanikzai; Mohammad Hashim Wafa; Abdul Wahed Wasiq; Hadia Sayam (Obstetrics and Gynecology International)
Background. Women’s and children’s health is a crucial public health concern that epitomizes the universal platform for Sustainable Development Goals (SDGs). Appropriate and timely care during pregnancy can improve maternal and child health. Objectives. The present study aimed at determining the magnitude and determinants of antenatal care services’ utilization in Kandahar city. Methods. A community-based cross-sectional study involving 850 women with at least one delivery in the last 2 years was carried out in Kandahar city from January to February 2021. Questionnaires to record information on sociodemographic, reproductive, and antenatal care- (ANC-) related characteristics were administered. Data were analyzed using SPSS 21.00 statistical software. We used descriptive statistics such as frequency and percentages to present the data. Determinants of antenatal care services’ utilization were determined using a multivariable logistic regression model. Results. Among all study participants, 589 (69.3%, 95% confidence interval (CI) = 66.0%–72.4%) of study participants utilized antenatal care services at least once. However, only 22% of the women were utilizing the recommended ≥4 ANC visits. Factors that remained significantly associated with antenatal care services’ utilization in multivariable analysis included women’s educational status (adjusted odds ratio (AOR) = 2.0, 95% CI: 1.0–4.3), pregnancy intention (AOR = 2.1, 95% CI: 1.1–3.4), and place of residence (AOR = 1.7, 95% CI: 1.1–2.6). Conclusion. This study has found high rates (vs. the national level) of antenatal care services’ utilization among women who had at least one delivery in the last 2 years. However, the rate of recommended ≥4 ANC visits was low. Factors determining antenatal care utilization such as educational status of the mother, pregnancy intention, and place of residence hold the key to address the issue of ANC services lower utilization and consequently improve maternal and fetal health.